Irreverencia, desatino y heterogeneidad en Pretérito Perfecto de Hugo Foguet (Revista de Crítica Literaria Latinoamericana, 2015)
"The novel Perfect Preterite by Hugo Foguet appears in the map of Argentinian literature as a piece of writing that, at the moment of its publication (1983) and from the periphery of the canon, breaks apart from any expected narrative produced inland, that is, a kind of realism that presented remote, still and atavistic provincial towns. This paper analyzes Foguet’s text from the notion of folly realism, coined by Eduardo Rosenzvaig in the context of the Argentinian and Latin American literature."
Keywords: Heterogeneity; Argentinian novel; Latin American novel; Foolish realism; Canon